EARLY SUPPLIER INVOLVEMENT AND SUPPLY CHAIN PERFORMANCE IN FOOD AND BEVERAGE PROCESSING COMPANIES IN KENYA - Benedict Mutinda Kimwaki (International Journal of Innovative Technologies in Social Science, 2022)
Early supply involvement is the process of engaging the supplier early enough before the orders are placed to identify the best approaches to use as both parties to meet the customer needs and reduce lead time and waiting time. This paper seeks to establish the influence of early supplier involvement on the supply chain performance of food and beverage processing companies in Kenya. Food and beverage processing companies have been at the stake of declined performance which has mainly been among other reasons as result of continued poor customer satisfaction and increased operational costs. This paper therefore seeks to assess the role played by early supplier involvement in the supply chain performance of these firms. A descriptive survey research approach was used in this study where the target population was 187 food and beverage processing companies in Kenya. A purposive sampling was used to ample 153 food and beverage processing companies in Nairobi. The heads of procurement in these companies were surveyed using a structured questionnaire. The collected data was analysed through descriptive and inferential statistics using SPSS. The findings from the study revealed that the involvement of suppliers early in designing the products and sharing with the suppliers the right information on customer specifications early reduce lead time. The study concluded early supplier involvement, process automation had a positive and significant influence of supply chain performance of food and beverage processing companies hence these companies through the management should uphold early supply involvement through sharing information with the suppliers and consulting them when designing and seeking raw materials for the production of customers’ orders. The findings from this study would be significant to the supply chain practitioners, the manufacturing sector in Kenya, the policy makers and the academic and research fraternity.